CD40, autophagy and Toxoplasma gondii - Carlos S Subauste (Memorias do Instituto Oswaldo Cruz, 2009)
Toxoplasmagondii represents a pathogen that survives within host cells by preventing the endosomal-lysosomal compartments from fusing with the parasitophorous vacuoles. The dogma had been that the non-fusogenic nature of these vacuoles is irreversible. Recent studies revealed that this dogma is not correct. Cell-mediated immunity through CD40 re-routes the parasitophorous vacuoles to the lysosomal compartment by a process called autophagy. Autophagosome formation around the parasitophorous vacuole results in killing of the T. gondii. CD40-induced autophagy likely contributes to resistance against T. gondii particularly in neural tissue.